Cyclin E Overexpression in Human Mammary Epithelial Cells Promotes Epithelial Cancer-Specific Copy Number Alterations - Giraldez, Servando (iScience, 2019)
Cyclin E, a key cell cycle regulatory protein, has been linked to oncogenesis when dysregulated. We have previously shown that overexpression of cyclin E causes replication stress, leading to failure to complete replication at specific chromosomal loci during S phase of the cell cycle. This in turn promotes chromosomal damage during anaphase. Here we show that non-transformed human mammary epithelial cell clones that survive such aberrant mitoses have a specific and reproducible pattern of chromosomal Copy Number Alterations (CNAs) that we have characterized and termed the cyclin E CNA signature. Using a number of computational approaches, we show that this signature resembles one specific CNA pattern enriched in differentiated epithelial-like tumors of the breast and ovary. Analysis of the CNA profile of these clones provides a potential mechanism for cyclin E-mediated oncogenesis.